Adopting mobile internet: a demographic and usage perspective. (30th June 2008) - Jiang, Pingjun
Based on an online survey of American consumers, the author found that mobile internet adopters tended to be younger, non-Caucasian, lower income, single male with higher career mobility. Surprisingly, contrary to fixed internet adoption, education played no significant role in predicting mobile internet adoption. Heavy mobile phone users were more likely to adopt mobile internet. On the opposite, heavy fixed internet users were less likely to adopt mobile internet. Interestingly, the demographics and usage patterns of consumers who perceived higher importance of having mobile internet capabilities did not match those of who indicated higher likelihood of adopting mobile internet.